2018
DOI: 10.7717/peerj.5523
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection effect of povidone-iodine in aquaculture water of swamp eel (Monopterus albus)

Abstract: The swamp eel (Monopterus albus) is an important commercial farmed fish species in China. However, it is susceptible to Aeromonas hydrophila infections, resulting in high mortality and considerable economic loss. Povidone-iodine (PVP-I) is a widely used chemical disinfectant in aquaculture, which can decrease the occurrence of diseases and improve the survival. However, environmental organic matter could affect the bactericidal effectiveness of PVP-I, and the efficacy of PVP-I in aquaculture water is still unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Mucus also contains immunoglobulins and lysozymes which have also antibacterial action, so groups 1 and 2 showed a considerable in vitro antibacterial activity against A. hydrophila but the presence of iodine is potentiating this action. Accordingly, Chen et al (2018) indicated that 10 ppm and 20 ppm of povidone-iodine effectively killed 99 and 100% of A. hydrophila in vitro and protected swamp eel (Monopterus albus).…”
Section: Discussionmentioning
confidence: 99%
“…Mucus also contains immunoglobulins and lysozymes which have also antibacterial action, so groups 1 and 2 showed a considerable in vitro antibacterial activity against A. hydrophila but the presence of iodine is potentiating this action. Accordingly, Chen et al (2018) indicated that 10 ppm and 20 ppm of povidone-iodine effectively killed 99 and 100% of A. hydrophila in vitro and protected swamp eel (Monopterus albus).…”
Section: Discussionmentioning
confidence: 99%
“…These chemicals are regularly employed in the majority of fish and shrimp hatcheries, grow-out facilities, and processing facilities to eliminate bacteria, viruses, and other pests that may negatively affect production. Depending on the nation, laws regulating the use of disinfectants may vary from being very easy to being quite difficult to understand (Chen et al, 2018;Kim et al, 2008;Pomaranski and Soto, 2020). The current study revealed Timsen and Pahonil were the most popular disinfectant in the aquaculture setup in the south eastern Bangladesh.…”
Section: Discussionmentioning
confidence: 63%
“…It is one of the most economically important freshwater fishes in East Asia because of its medicinal and food value (Zhou et al, 2002). M. albus is affected by the bacterial pathogen Aeromonas hydrophila ( A. hydrophila ), causing disease that could be responsible for major economic losses in the aquaculture industry (Chen, Lai, Wang, Wei, & Zhong, 2018). A. hydrophila infection can be treated with antibiotics, but this has raised concerns regarding antibiotic resistance and public health security due to antibiotic residue in fish and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most economically important freshwater fishes in East Asia because of its medicinal and food value (Zhou et al, 2002). M. albus is affected by the bacterial pathogen Aeromonas hydrophila (A. hydrophila), causing disease that could be responsible for major economic losses in the aquaculture industry (Chen, Lai, Wang, Wei, & Zhong, 2018).…”
Section: Introductionmentioning
confidence: 99%